Progress in pH-Sensitive sensors: essential tools for organelle pH detection, spotlighting mitochondrion and diverse applications - Li, Shu-Ang; Meng, Xiao-Yan; Zhang, Ying-Jie; Chen, Cai-Li; Jiao, Yu-Xue; Zhu, Yong-Qing; Liu, Pei-Pei; Sun, Wei (Frontiers in Pharmacology, 2024)
pH-sensitive fluorescent proteins have revolutionized the field of cellular imaging and physiology, offering insight into the dynamic pH changes that underlie fundamental cellular processes. This comprehensive review explores the diverse applications and recent advances in the use of pH-sensitive fluorescent proteins. These remarkable tools enable researchers to visualize and monitor pH variations within subcellular compartments, especially mitochondria, shedding light on organelle-specific pH regulation. They play pivotal roles in visualizing exocytosis and endocytosis events in synaptic transmission, monitoring cell death and apoptosis, and understanding drug effects and disease progression. Recent advancements have led to improved photostability, pH specificity, and subcellular targeting, enhancing their utility. Techniques for multiplexed imaging, three-dimensional visualization, and superresolution microscopy are expanding the horizon of pH-sensitive protein applications. The future holds promise for their integration into optogenetics and drug discovery. With their ever-evolving capabilities, pH-sensitive fluorescent proteins remain indispensable tools for unravelling cellular dynamics and driving breakthroughs in biological research. This review serves as a comprehensive resource for researchers seeking to harness the potential of pH-sensitive fluorescent proteins.